2005
DOI: 10.1115/1.2000271
|View full text |Cite
|
Sign up to set email alerts
|

Navier–Stokes Analysis of a Regular Two-Dimensional Roughness Pattern Under Turbulent Flow Regime

Abstract: The present work deals with the flow characteristics induced by a two-dimensional textured surface. The texture consists of identical and equally spaced rectangles with characteristic lengths at least one order of magnitude larger than the clearance of the thin film. Periodic boundary conditions enable the analysis of a single groove and the complete Navier–Stokes analysis is carried on for turbulent flow Reynolds numbers. The analysis is performed for shear driven flows (Couette), pressure driven flows (Poise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The dimensionless shear stress is plotted with Couette and Poiseuille flows [6], the friction coefficient, leakage for different shapes of asperities are obtained [5]. But all these studies have not been interested to micro-asperity sizing.…”
Section: Discussionmentioning
confidence: 99%
“…The dimensionless shear stress is plotted with Couette and Poiseuille flows [6], the friction coefficient, leakage for different shapes of asperities are obtained [5]. But all these studies have not been interested to micro-asperity sizing.…”
Section: Discussionmentioning
confidence: 99%
“…However, the flow is often turbulent (for the Reynolds numbers > 1000) especially in high speed bearings. The Reynolds averaged Navier-Stokes equations can be used to describe turbulent flows for roughened surfaces 43,44) . The unified approach will also be extended into PDEs in order to include turbulent flow effects.…”
Section: Discussionmentioning
confidence: 99%
“…Fluid inertia is a universal phenomenon of fluid mechanics in hydrodynamic lubrication. Billy et al [2][3] indicated that fluid inertia can cause fluid recirculation and affect the fluid pressure buildup, resulting in a net load-carrying capacity (LCC) for textured surfaces. Cupillard et al [4] pointed out that it may also reduce the LCC, which is closely related to the texture geometric parameters.…”
Section: Introductionmentioning
confidence: 99%